Design and characterization of plasticized bacterial cellulose/waterborne polyurethane composite with antibacterial function for nasal stenting. Issue 6 (15th October 2020) - Feng, Zhaoxuan; Li, Minglu; Jin, Xing; Zheng, Yudong; Liu, Junxiu; Zhao, Liang; Wang, Yansen; Li, Hao; Zuo, Danlin
Abstract: A nasal stent capable of preventing adhesions and inflammation is of great value in treating nasal diseases. In order to solve the problems of tissue adhesion and inflammation response, we prepared plasticized bacterial cellulose (BCG) and waterborne polyurethane (WPU) composite with antibacterial function used as a novel nasal stent. The gelation behavior of BCG could contribute to protecting the paranasal sinus mucosa; meanwhile, the WPU with improved mechanical property was aimed at supporting the narrow nasal cavity. The thickness, size and the supporting force of the nasal stent could be adjusted according to the specific conditions of the nasal. Thermogravimetric analysis, contact angle and water absorption test were applied to investigate the thermal, hydrophilic and water absorption properties of the composite materials. The composite materials loaded with poly(hexamethylene biguanide) hydrochloride maintained well antibacterial activity over 12 days. Animal experiments further revealed that the mucosal epithelium mucosae damage of BCG−WPU composite was minor compared with that of WPU. This new type of drug-loaded nasal stent can effectively address the postoperative adhesions and infections while ensuring the health of nasal mucosal, and thus has an immense clinical application prospects in treating nasal diseases.